PF4 regulates neuronal ferroptosis in cerebral hemorrhage through CXCR3/PI3K/AKT/Nrf2 pathway - Na Hu; Yunfeng Li; Guohong Zhang; Wei Wang; Liping An; Ran An; Yu Liu (Biomolecules & Biomedicine)
Inhibiting ferroptosis represents a promising strategy for managing neuronal injury caused by intracerebral hemorrhage (ICH). Platelet factor 4 (PF4), a chemokine with diverse biological functions, has an unclear role in ICH and its impact on neuronal ferroptosis. To investigate this, a hemin-induced injury model was established in PC12 cells in vitro, and an ICH model was created in vivo using IV collagenase injection. Hemin-treated PC12 cells were co-cultured with recombinant mouse PF4 (Rm-PF4) protein to examine the effects of PF4 on ferroptosis. Additionally, Rm-PF4 was administered intraperitoneally to ICH mice, and its influence on neurological dysfunction, brain edema, and neuronal ferroptosis was evaluated. Western blot analysis was employed to assess PF4 levels, CXCR3/phosphatidylinositol 3-kinase (PI3K)/AKT/nuclear factor erythroid-2-related factor 2 (Nrf2) pathway activation, and ferroptosis-related protein expression. PF4 levels were found to be reduced in both perihematomal brain tissues of ICH mice and hemin-treated PC12 cells. Treatment with Rm-PF4 decreased ferrous ion, malondialdehyde (MDA), and reactive oxygen species (ROS) levels, effectively inhibiting ferroptosis in PC12 cells. Furthermore, Rm-PF4 administration alleviated neurological dysfunction, neuronal damage, and brain edema while suppressing neuronal ferroptosis in ICH mice. Mechanistically, Rm-PF4 activated the CXCR3/PI3K/AKT/Nrf2 pathway, and this protective effect was diminished by a CXCR3 antagonist in both ICH mice and hemin-treated PC12 cells. In conclusion, PF4 mitigates ICH-induced neuronal ferroptosis in mouse models and PC12 cells by activating the CXCR3/PI3K/AKT/Nrf2 pathway.